ANALISIS KONOTASI PADA LIRIK LAGU DALAM ALBUM DIGDAYA KARYA LAZE - Khairul Rizky; Hasnah Faizah; Oki Rasdana (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2026)
Song lyrics often employ non-literal meanings, particularly connotative meaning, as a medium for conveying messages. This study aims to identify and describe the types of connotative meanings found in the song lyrics of the Digdaya album by Laze and to explain their role in message delivery. This research applies a qualitative approach using a descriptive method. The data consist of words, phrases, and sentences containing connotative meanings taken from 13 songs in the Digdaya album. Data were collected through documentation techniques using listening, reading, and note-taking methods, while data analysis was conducted using Creswell’s spiral analysis technique. The results reveal 187 instances of connotative meaning, comprising 85 positive connotations and 102 negative connotations. These findings indicate that connotative meaning plays an important role in constructing emotional expression, conveying social criticism, and enhancing the depth of meaning in rap song lyrics.